Assessment of training status in elite boxers - Swiecicki, L.; Klukowski, K.; Hübner-Wozniak, E. (Medicina Sportiva, 2013)
To examine boxer`s performance in a special exercise test in normoxia and moderate hypoxia, and to evaluate the usefulness of daily plasma urea concentration and creatine kinase activity estimation for monitoring of training in national level boxers. Methods: The study included 18 healthy elite boxers, who performed a special exercise test under normobaric and hypobaric conditions. During the test, the heart rate and power output were monitored and the total mechanical work (TMW, kJ) was recorded. Every morning during nine days of training camp blood from earlobe was taken in preprandial state to assess urea level and creatine kinase activity. Results: The boxer, whose training level was the highest, maintained higher values of the mean power (W) than the group, particularly in the second round of workload, both in normoxia and hypoxia conditions. The reduction of TMW for the whole group and the champion in both types of conditions was similar (25,5 and 25,4%, respectively). The direction of changes in the plasma urea level during the period of study was not dependent on the daily training loads and was similar for the whole group and the competitor with the highest oxygen consumption. The direction of changes in creatine kinase activity was similar for the whole group, the champion competitor, and the competitor with the highest VO2max. Conclusions: Findings from the present study indicate that the results of a specific exercise test both in moderate hypoxia and in normoxia depended on the athlete`s training status. Daily morning measurements of plasma CK activity appear to be a useful tool for monitoring training, despite a varied body response to effort stimuli, while process of changes in plasma urea concentration indicated the influence of factors other than the magnitude of training loads. Gathering data related to fitness and biochemical parameters can help coaches and athletes improve performance and prevent muscle overload.